2014
DOI: 10.1007/s00066-014-0650-0
|View full text |Cite
|
Sign up to set email alerts
|

Complete pathological responses in locally advanced rectal cancer after preoperative IMRT and integrated-boost chemoradiation

Abstract: The IMRT and integrated-boost chemoradiation scheme offered higher rates of ypCR and pT downstaging, without a significant increase in toxicity. The circumferential margins were free of tumors in the majority of patients. Primary tumor regression was associated with better disease-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 30 publications
3
34
0
1
Order By: Relevance
“…To the best of our knowledge, Hernando-Requejo et al reported excellent pCR rates using the concomitant-boost IMRT dose fractionation scheme (35). Seventy-four patients were treated with concomitant-boost IMRT (57.5 Gy in 23 fractions and concurrent 825 mg/m 2 Cap bid), and the pCR and grade 3 toxicity rates were 30.6 and 17.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, Hernando-Requejo et al reported excellent pCR rates using the concomitant-boost IMRT dose fractionation scheme (35). Seventy-four patients were treated with concomitant-boost IMRT (57.5 Gy in 23 fractions and concurrent 825 mg/m 2 Cap bid), and the pCR and grade 3 toxicity rates were 30.6 and 17.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Positive outcomes due to IMRT plus Cap treatment have been observed, with pCR rates ranging from 14.1% to 30.6% in patients with grade 3 disease, who comprised 11.1% to 17.6% of the study populations (3335), but these studies did not mention cases of PD. Lu et al (36) only reported a pCR in 20% of the cases with a 22% rate of grade 3 toxicity, and PD in 17% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…Most articles about IMRT were anal cancer or nonspecific locations of rectum. [10,25,26] Till now, no article demonstrates the outcomes of neoadjuvant CCRT for lower 3rd rectal cancer with conventional fraction IMRT and concurrent fluoropyrimidine CT. Five-year overall survival rate, disease-free survival rate, and local recurrence rate for lower rectal cancer patients in group II were 70%, 70%, and 3%, respectively (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Early data from retrospective series and phase II trials suggest good compliance, low rates of acute bowel toxicity, and high complete pathologic response rates after preoperative IMRT with concurrent fluoropyrimidine therapy. [1013] However, there are no randomized trials comparing IMRT with conventional 3D-CRT, and its routine use cannot yet be recommended.…”
Section: Introductionmentioning
confidence: 99%
“…anal cancer, and has previously been integrated into the neoadjuvant treatment of locally advanced rectal cancer [32][33][34]. As such, many of the technical challenges of treatment delivery are well understood, including estimation of treatment margins and use of imaging for treatment verification.…”
Section: External Beam Radiotherapymentioning
confidence: 99%